2020
DOI: 10.1371/journal.ppat.1008899
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 infection leads to neurodevelopmental disorder-associated neuropathological changes

Abstract: Neonatal herpes simplex virus type 1 (HSV-1) infections contribute to various neurodevelopmental disabilities and the subsequent long-term neurological sequelae into the adulthood. However, further understanding of fetal brain development and the potential neuropathological effects of the HSV-1 infection are hampered by the limitations of existing neurodevelopmental models due to the dramatic differences between humans and other mammalians. Here we generated in vitro neurodevelopmental disorder models includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 46 publications
7
46
0
Order By: Relevance
“…However, at the highest infectious dose, all neuronal cell bodies for each strain had detectable viral protein consistent with productive replication ( S2 Fig ). This finding is in accordance with prior studies demonstrating that high multiplicities of infection are necessary to uniformly infect neurons with alphaherpesviruses [ 58 61 ]. For samples used in the RNA-sequencing analysis, differentiated SH-SY5Y human neuronal cells were infected with purified virions of HSV-1 strain KOS, F, or McKrae at 1.6e 7 PFU/dish to ensure synchronous infection.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, at the highest infectious dose, all neuronal cell bodies for each strain had detectable viral protein consistent with productive replication ( S2 Fig ). This finding is in accordance with prior studies demonstrating that high multiplicities of infection are necessary to uniformly infect neurons with alphaherpesviruses [ 58 61 ]. For samples used in the RNA-sequencing analysis, differentiated SH-SY5Y human neuronal cells were infected with purified virions of HSV-1 strain KOS, F, or McKrae at 1.6e 7 PFU/dish to ensure synchronous infection.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, we observed the activation of host immune responses, including genes involved in pathways such as death receptor signaling and retinoic acid-mediated apoptosis signaling ( Fig 1B ). Broadly, these findings are in agreement with previous findings indicating the induction of host immune pathways with neuronal HSV-1 infection and latency, and the altered activation of neuronal cell adhesion and migration pathways [ 17 , 19 21 , 23 , 24 , 61 ].…”
Section: Discussionsupporting
confidence: 92%
“…They exhibit neuronal heterogeneity and lamina-like structure [ 839 ]. Brain organoids can be infected with HSV-1 and exhibit inflammation, HSV-1 can establish hallmarks of latency in such cultures in the presence of antivirals like interferon (IFN), and HSV-1 can infect the outer laminar structure of these organoids moving further inside after infection [ 840 , 841 ]. All these elements make the use of brain organoids in HSV-1 research attractive.…”
Section: Resultsmentioning
confidence: 99%
“… 213 , 214 HSV-1-infected cerebral organoids confirmed that the virus impairs neuronal differentiation and cortical layering, as well as revealed the abnormal increase in microglial proliferation and specific inflammatory factors. 148 …”
Section: Brain Organoid Models For Covid-19 and Infectious Diseasesmentioning
confidence: 99%
“…213,214 HSV-1-infected cerebral organoids confirmed that the virus impairs neuronal differentiation and cortical layering, as well as revealed the abnormal increase in microglial proliferation and specific inflammatory factors. 148 Brain organoids have even been exploited to investigate non-virus pathogens. Sporadic Creutzfeldt-Jakob Disease (sCJD), a transmissible neurodegenerative disease targeting several brain regions and caused by infectious prions, was shown with cerebral organoids to increase metabolism, LDH release, and cytokine release.…”
Section: Brain Organoid Models For Covid-19 and Infectious Diseasesmentioning
confidence: 99%